Call the midwife. Season four [videorecording (DVD)] - Redgrave, Vanessa, 1937-; Agutter, Jenny; Ferris, Pam; Hart, Miranda, 1972-; Worth, Jennifer, 1935-2011 (BBC, 2015)
Now nearing the 1960s, the community enters a new time of social change, while stories of birth, life and death continue to touch your heart. Will live-wire Nurse Trixie marry her young curate? What new project calls for a heart as big as Chummy's? How will Sister Evangelina react to two new nurses? And why does Sister Julienne appear so unsettled by a mystery benefactor?